Comparative Study on OVOP of Japan and OTOP of Thailand: Lesson Learned for Myanmar Narratives - Thaung Htet, Atar (International Journal of Law Policy and Governance, 2025)
This study intends to examine the one village – one product public policy process by comparing the Thailand’ OTOP scheme and Japan’ s OVOP scheme. The multiple stream model used to analyze the problem identification and agenda setting, very first part of public policy process. For analysis the second part of public policy namely policy formulation, iron triangle model was used. There are two types of public policy implementation approach – Bottom- up and top- down. These kinds of approach used for the policy implementation analysis. The first findings of this comparative analysis where 1997 financial crisis is obvious problem for OTOP and economic stagnation of Oita prefecture is major cause for OVOP agenda setting. In policy formulation process, Thailand OTOP is formed by iron triangle because of Thaksin and TRT party won the election and take the major role for coordination of iron triangle mechanism. In one side, OVOP is advocated solely by Hiramatsu not aligned with iron triangle. OTOP used the Top – down policy implementation approach and OVOP used the Bottom -UP approach for policy implementation. According the result of comparative analysis, Myanmar can learn the lessons for their one village one product scheme initiatives for forthcomings.